2015
DOI: 10.3390/ijerph120809068
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Effect of Ambient Temperature and the Risk of Stroke: A Systematic Review and Meta-Analysis

Abstract: Background and Purpose: The relationship between stroke and short-term temperature changes remains controversial. Therefore, we conducted a systematic review and meta-analysis to investigate the association between stroke and both high and low temperatures, and health assessment. Methods: We searched PubMed, Embase, Cochrane, China National Knowledge Infrastructure (CNKI) and Wanfang Data up to 14 September 2014. Study selection, quality assessment, and author-contractions were steps before data extraction. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
106
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(118 citation statements)
references
References 70 publications
9
106
0
3
Order By: Relevance
“…The statistical model was adjusted by temperature and relative humidity, given that these meteorological variables are reported to be associated with the risk of stroke. 21 We used natural cubic splines with 3 df to model the nonlinear effects of temperature and relative humidity on the concurrent day of hospital admission. 15 Because prior research has found that fewer strokes occur on holidays, 22 we controlled for public holidays using binary variable (coded as public holiday = 1 and no public holiday = 0) in the model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The statistical model was adjusted by temperature and relative humidity, given that these meteorological variables are reported to be associated with the risk of stroke. 21 We used natural cubic splines with 3 df to model the nonlinear effects of temperature and relative humidity on the concurrent day of hospital admission. 15 Because prior research has found that fewer strokes occur on holidays, 22 we controlled for public holidays using binary variable (coded as public holiday = 1 and no public holiday = 0) in the model.…”
Section: Discussionmentioning
confidence: 99%
“…Conditional logistic regression was used to perform the time‐stratified case‐crossover design. The statistical model was adjusted by temperature and relative humidity, given that these meteorological variables are reported to be associated with the risk of stroke . We used natural cubic splines with 3 df to model the nonlinear effects of temperature and relative humidity on the concurrent day of hospital admission .…”
Section: Methodsmentioning
confidence: 99%
“…It is thought that temperature variations can alter blood viscosity and coagulability, which can increase risk of stroke (Kyobutungi et al 2005). Interestingly, a systematic review considering effect of temperature did not find a positive association between heat and stroke morbidity (Lian et al 2015). Further work should be conducted to confirm our findings and explore the potential effect of climatic variability on hospitalizations for ischemic stroke.…”
Section: Discussionmentioning
confidence: 60%
“…During the recent decade, many studies have focused on the impact of weather on the morbidity from stroke, and several meta-analyses or reviews were carried out [1][2][3][4][5]. Air temperature (T) and atmospheric pressure (AP) are among the most closely studied weather variables; increases, decreases, and uctuations in both have been signi cantly linked to numerous stroke subtypes.…”
Section: Introductionmentioning
confidence: 99%
“…The daily T changes have also been associated with the risk of stroke. The results of a meta-analysis have shown that a daily increase in T was a protective factor against HS, and an increase as well as a decrease in daily T acted as a risk factor for IS [1].…”
Section: Introductionmentioning
confidence: 99%